ISIS : Inside the Army of Terror - Weiss, Michael (Michael Douglas) and Hassan, Hassan (New York Regan Arts, 2015)
"How did a group of religious fanatics, clad in black pajamas and armed to the teeth, manage to carve out a violent, fundamentalist "Islamic state" in wide swaths of Syria and Iraq? How did the widely celebrated revolution against Syrian dictator Bashar Assad descend into a movement led by a psychopathically violent band of jihadists dedicated to the destruction of America? And just who are these brutal Islamic militants--many speaking unaccented English and holding European passports--beheading Western hostages in slickly produced videos? In Isis: Inside the Army of Terror, Syrian journalist Hassan Hassan and American analyst Michael Weiss explain how the terrorists of ISIS evolved from a nearly defeated insurgent group into a jihadi army--armed with American military hardware and the capability to administer a functioning state. Weiss and Hassan, who have both been on the frontlines of the Syrian revolution, have interviewed dozens of experts, American military and intelligence officials, and ISIS fighters to paint the first comprehensive picture of the rise and expansion of America's most formidable terrorist enemy. ISIS: Inside the Army of Terror is destined to become the standard text on a terror group that, unfortunately, shows no signs of going away"
Include Epilouge
Keywords: Terrorism -- Terrorists -- Middle East